2005
DOI: 10.1016/j.jvs.2005.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysm formation in a subset of patients with small intestinal submucosa biologic patches after carotid endarterectomy

Abstract: Biologic patches that undergo active remodeling in the carotid artery require greater thickness than was anticipated to decrease wall stress and suture hole elongation. Patches exceeding this minimum thickness will be required to ensure the safety of new SIS patch designs for vascular operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 22 publications
2
27
1
Order By: Relevance
“…The same encouraging results were not obtained in the clinical experience by McCready, who reported seven episodes of patch aneurysm among 76 patients who had undergone patch angioplasty of the carotid artery following endoarterectomy [3]. The patch used in this latter study was another SIS-ECM product (Surgisis ® by Cook Surgical, Bloomington, IN, USA) that was thinner than CorMatrix.…”
supporting
confidence: 66%
“…The same encouraging results were not obtained in the clinical experience by McCready, who reported seven episodes of patch aneurysm among 76 patients who had undergone patch angioplasty of the carotid artery following endoarterectomy [3]. The patch used in this latter study was another SIS-ECM product (Surgisis ® by Cook Surgical, Bloomington, IN, USA) that was thinner than CorMatrix.…”
supporting
confidence: 66%
“…We think that a closed environment around the defect site was created and inflammatory cells were trapped, leading to a consistent histological picture [1]. Other recent human and experimental studies have reported similar effects of SIS [5,13]. Helton et al [5] investigated the potential role of SIS in open and laparoscopic repair of incisional hernia.…”
Section: Discussionmentioning
confidence: 81%
“…The authors reported mesh infection (reaction) in four of 22 patients from the best (=clean) wound group and an overall recurrence rate of 17% within a 14-month median observation period. Furthermore, rapid shrinking of SIS (>40% in 8 weeks) was described by Poulose et al [20] and might also have played a role in the SIS-related formation of pseudoaneurysm in carotid endarterectomy described by McCready et al [13]. It is obvious that the questions arising from these observations have to be fully elucidated prior to routine clinical use of SIS in hernia repair.…”
Section: Discussionmentioning
confidence: 93%
“…It is gradually resorbed by the host organism and subsequently replaced by host tissue (12,17). Following extensive experimental investigations, porcine small intestinal submucosa has been successfully used clinically in various fields of soft tissue augmentation, to treat hernias and in tendon repair (18 -20), stress urinary incontinence (21), leg ulcers (22), plastic surgery (23), and vascular surgery (24).…”
Section: Discussionmentioning
confidence: 99%